REPORT ON PARTICIPATION IN THE CONFERENCE «Biological Control of Plant Pathogens», IOBC, Reims, France, 24-27 June 2012 - T. P. Suprunova; N. A. Shmykova (Овощи России)
June 24-27, 2012 in Reims (France) the International conference was held devoted to biological control of plant pathogens in an environmentally safe agriculture. The conference was held at the University of Reims (Universite de Reims Champagne Ardenne, France).